Faktor yang berhubungan dengan kualitas hidup pasien hemodialisis di rumah sakit swasta Yogyakarta - Tatik Pujiastuti; Chatarina Setya Widyastuti (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Hemodialysis (HD) is one of the procedures to replace the excretion function due to kidney failure. The successful management of hemodialysis is very important to improve the quality of life. There was a relationship between various factors with the quality of life, including hemoglobin levels, age, sex, duration of hemodialysis and Interdialitic Weight Gain (IDWG). Objective: The purpose of the research is to determine factors correlated to the quality of life in hemodialysis patients. Methods: This is quantitative research. The Sixty-five patients on hemodialysis were randomly selected in the hemodialysis unit. Samples will be interviewed with a quallity of life questionnaire for hemodialysis. Statistical analysis with univariat and Spearman correlation. Results: Based on the Spearman correlation test showed that statistically, there was a significant correlation between age and quality of life: Mental Component (MC) with p-value of 0.017 <0.05, duration of undergoing hemodialysis with quality of life: Physical Component (PC) with p-value 0.034 <0.05, and IDWG with quality of life: Effect of Kidney Disease (EKD) with p-value 0.004 <0.05. Conclusion: It is assumed that age, duration of hemodialysis, and IDWG are related to the quality of life among hemodialysis patients. Based on the result, it is suggested for nurses to educate about hemodialysis.